Pan-cancer analysis reveals a regulatory pattern of anoikis in human cancers: Anoikis regulation in human cancers - Wang, Xiaoyun; Yang, Chao; Wang, Xingjian; Duan, Pengfei (Cellular and Molecular Biology, 2024)
Anoikis emerges when a cell finds itself extricated from the appropriate extracellular matrix, leading to an interruption in integrin ligation and thus triggering programmed cellular demise. The cardinal role of Anoikis in the realms of tumor invasion and metastasis is undeniable, although our grasp on its precise influence within the convoluted landscape of cancer biology remains somewhat circumscribed. Notably, both the immune milieu of the tumor and its inherent aggression are correlated with the fluctuating variables of Anoikis. We conducted a thorough evaluation of the genes associated with anoikis and studied the regulatory patterns of these genes as well as the prognostic impact of anoikis in 33 different types of tumors. We provided functional annotations for the regulatory patterns linked to Anoikis. Additionally, we described the associations between immunological factors and genes associated with Anoikis. By applying gene set variation analysis (GSVA), we utilized the inherent abilities of 34 basic genes to calculate the Anoikis index. The Anoikis index is closely related to prognosis, immune microenvironment, immunotherapy, and other aspects. Our functional research revealed a correlation between immune cell infiltration, EMT, and a regulatory gene that is synonymous with adverse survival outcomes. In addition, our observations revealed a direct relationship between the expression of CEACAM5 and CEACAM6,the amplification of epithelial mesenchymal transition (EMT) phenomenon, and a decrease in survival outcomes.The potential therapeutic utility of anoikis-related genes was highlighted by the possible links between TME, clinical samples, genetic mutations, drug resistance, and immunotherapy.